Telerilevamento e GIS per la valutazione e il monitoraggio delle isole di calore in ambiente urbano - Adelfio, Sabrina; Enea, Caterina; Bazan, Giuseppe; Orlando, Pietro (GEOmedia, 2017)
The techniques of spatial analysis and Remote Sensing represent an useful tool for the knowledge and the study of the Urban Heat Island phenomenon (English acronym UHI). In this study, among the different causes that lead to the generation of the event, those regarding physical features of the surface and the presence of different land use/cover such as: the high cover of urban areas and the lack of green areas have been examined. The Remote Sensing techniques allow to create maps of the land use/cover, then, in order to estimate the different in temperature due to the distance to the vegetation, the temperature of the bodies already tested have been compared with a thermal map. In detail the aim of the research is to examine the presence of the phenomenon in Palermo, through the analysis of portion of soil with different morphological features.